Prioritas Pengembangan dan Pengelolaan Jaringan Irigasi dengan Metode Multiple Attribute Decision Making di UPT SDA Jenggawah pada Daerah Irigasi Talang Kabupaten Jember - Amelia Tri Arsita (Fakultas Pertanian, 2026)
Water availability is an important factor in maintaining food security and is greatly influenced by the performance of irrigation systems. Suboptimal insfrastructure and limited maintenance budgets often pose obstacles to the distribution of water to agricultural land. Therefore, a systematic approach is needed to determine the priorities for the development and management of irrigation networks. This study uses the Multiple Attribute Decision Making (MADM) method, namely Simple Additive Weighting (SAW), Weighted Product (WP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The alternatives analyzed include the irrigation network at the Jenggawah Water Resource Management Unit based on five criteria: primary network insfrastructure, tertiary network insfrastructure, water availability, productivity, and service area. The results showed that the SAW and WP methods prioritized the Mayang Primary irrigation channel, while the TOPSIS method prioritized the Mayang Secondary irrigation channel. Sustainable maintenance and an increased institutional role for farmers are needed to support effective and sustainable irrigation management.
FINALISASI oleh Arif 2026 Mei 26
Keywords: irrigation network; MADM; irrigation development and management priorities